SPIDER-1 measurements (LP, GPS, SMILE) inside an aurora (Kungliga tekniska högskolan, 2021)
En serie CSV-filer som innehåller en del av mätningen utförd av SPIDER-1 raket. Raketen lanserades kl.21: 09UT den 2 februari 2016 från Esrange (Kiruna, Sverige) och kastades ut 10 Free Falling Units (FFUs) inuti en västerutgående aurora. Varje FFU var utrustad med en utvecklingsbar Langmuir-sond (LP) för att mäta plasmagenskaperna (elektrontätheten ne, elektrontemperaturen Te och plasmapotentialen Vp), samt en 3-axlig fluxgate magnetometer (SMILE) som mäter den magnetiska fält och en positioneringsutrustning (GPS). Användbara data från två FFU (FFU02 och FFU06) presenteras, vilket användes i JGR-Space Physics-artikeln med namnet "Multi-point measurements of the plasma properties inside an aurora from the SPIDER sounding rocket." A series of CSV files containing some of the measurements performed by the SPIDER-1 sounding rocket inside an aurora. The rocket was launched at 21:09UT on February 2nd 2016 from Esrange (Kiruna, Sweden) and ejected 10 Free Falling Units (FFUs) inside a westward-traveling active aurora. Each FFU was equipped with a deployable Langmuir probe (LP) to measure the plasma properties (the electron density ne, the electron temperature Te, and the plasma potential Vp), as well as a 3-axis fluxgate magnetometer (SMILE) measuring the magnetic field and a positioning recorder (GPS). Usable data from two of the FFUs (FFU02 and FFU06) is presented, which was used in the JGR-Space Physics article named "Multi-point measurements of the plasma properties inside an aurora from the SPIDER sounding rocket."